Morphological features of benign pigmented ear lesions: a cross‐sectional study. (4th July 2021) - Rishpon, Ayelet; Sprecher, Eli; Dusza, Stephen W.; Kleinman, Elana; Haupt, Sara; Rabinovitz, Harold; Scope, Alon
Abstract: Background: The morphology of benign pigmented lesions on the ears has been scarcely studied. Methods: We prospectively screened all patients presenting to a pigmented lesion clinic at a tertiary academic hospital, between November 2015 and August 2016, for the presence of benign pigmented ear lesions. Clinical and dermoscopic images were obtained for all lesions. Additionally, we performed a retrospective analysis of reflectance confocal microscopy (RCM) of benign pigmented ear lesions and a retrospective analysis of clinical and dermoscopic findings of biopsy‐confirmed ear melanomas. Results: In total, 165 patients (median age 48, 53% female) contributed 708 benign pigmented ear lesions to the study. Participants with multiple body nevi and those with an atypical nevus phenotype (multiple body nevi and ≥ one atypical nevus) had a higher mean number of ear lesions than those without multiple body nevi (4.5 and 5.4 vs. 3.9, P  < 0.05). The most common diagnoses were nevus (35%) and solar lentigo (34%), followed by pigmented lentiginous macules (PLM) (27%). Dermoscopically scattered pigmented small globules/dots were observed in 30% of nevi and 17% of PLMs. RCM analysis of 24 ear lesions showed a comparable frequency of RCM‐clods between nevi and PLMs. Analysis of 29 ear melanomas revealed larger lesions with more complex dermoscopic patterns. Conclusion: Multiple body nevi, and particularly an atypical nevus phenotype, were associated with having more pigmented ear lesions. Based on RCM analysis, PLMs of the ear likely represent small nevi. Ear melanomas tend to be larger and dermoscopically complex compared to ear nevi.